Effect of Using Karuta Card on Students’ Ability to Comprehend Vocabulary (Experimental Research for the Seventh Grade at Sabilul Mukminin Boarding School Binjai) - Hanifa Azimah (Jurnal Pendidikan Indonesia, 2024)
The research question is: Is there an effect of using the Karuta card on students’ ability in the seventh grade at the Sabilul Mukminin Binjai Boarding School to comprehend vocabulary? Its purpose is to know the effect of using the Karuta card on students’ ability in the seventh grade at the Sabilul Mukminin Binjai Boarding School to comprehend vocabulary, especially to pronounce its letters correctly. The method used is quantitative field research of the experimental type, and the method used is a statistical method using SPSS 25 and a t-test. The result of this research is that the use of the Karuta card does not affect students’ ability in the seventh grade at the Sabilul Mukminin Binjai Boarding School to pronounce vocabulary correctly, and the author infers this from the results of the female students on the test in the experimental class and the control class. The average score for vocabulary comprehension in the control class was 72.68, which is higher than the average score for vocabulary comprehension in the experimental class, which was 64.85. From these two rates, t0 is found at 1,252 It is lower than ttable (2,026). Therefore, the null hypothesis is accepted, and the alternative hypothesis is rejected, meaning that the use of the Karuta card does not affect the ability of the female students of the seventh intermediate semester at the Sabeel Al-Muminin Benjay Institute to comprehend vocabulary, especially in pronouncing its letters correctly.